Failure in the mother-young communication in domestic mammals: endocrine and behavioral aspects - Mota-Rojas, Daniel; Bienboire-Frosini, Cécile; Bettencourt, Arthur Fernandes; Villanueva-García, Dina; Domínguez-Oliva, Adriana; Álvarez-Macías, Adolfo; Fischer, Vivian; Mora-Medina, Patricia; Olmos-Hernández, Adriana; Hernández-Avalos, Ismael; Martínez-Burnes, Julio; Abd El-Aziz, Ayman H.; et al. (Frontiers in Veterinary Science, 2025)
Mothering and bonding represent fundamental aspects of survival and development in domestic mammalian species. The mother-young interaction immediately after parturition is a critical event where the mother establishes selective care for the offspring, and the newborn responds to maternal stimulation. To develop this bond, maternal responses such as nest building, grooming, allowing suckling, or retrieval of the young need to be performed within the so-called sensitive period. This review discusses the factors that lead to failure in mother-young bonding in domestic mammals, analyzing mother- and young-related factors that might impair maternal recognition. Among these factors, endocrine aspects such as oxytocin impairments and lower release interfere with the expression of maternal behavior. Moreover, a complex network of hormonal regulators, including steroid hormones (estrogen, progesterone), prolactin, and dopamine, is required to modulate the parenting and attachment process. In addition, other biological aspects such as prenatal conditions, maternal nutritional state, parity, and environmental factors can affect the quality of maternal care. Regarding young-related factors, low vitality due to events such as meconium aspiration syndrome decreases the newborn’s motivation to interact and develop the mother-young bond. Recognizing these aspects to prevent offspring rejection is essential to neonatal survival. Peripartum monitoring and precision livestock farming are suggested methods to ensure appropriate mother-young communication.